Extracts from The Cochrane Library: vestibular rehabilitation for unilateral peripheral vestibular dysfunction (review). - Burton, M; Monsell, E; Rosenfeld, R (2008)
The "Cochrane Corner" is a quarterly section in the Journal that highlights systematic reviews relevant to otolaryngology--head and neck surgery, with invited commentary to highlight implications for clinical decision making. This installment features a Cochrane Review entitled "Vestibular rehabilitation for unilateral peripheral vestibular dysfunction," which concludes that there is moderate to strong evidence from high-quality randomized trials supporting the safety and efficacy of this intervention.